Shifting Rhetoric of Teej Songs in the Context of Consumer Culture in Nepal - Niraula, Sanjeev (SCHOLARS: Journal of Arts & Humanities, 2023)
This paper examines the influence of consumer culture behind the shifting rhetoric of the songs performed in Teej, a major festival for Hindu women in Nepal. By analyzing verbal and non-verbal elements in five selected Teej songs, two conventional songs and three modern songs, the study explores the shifting rhetoric of Teej songs. A comparative analysis is carried out to indicate how the modern Teej songs differ from the conventional ones. While the conventional songs deal with the women’s experience after marriage, their pain and agonies, and their desire to return to their parents’ home, the modern songs present themes of fashion, modern lifestyle and celebration. Drawing upon the insights of consumer culture of Steven Miles blending them with the concepts of cultural rhetoric of Tomás Albaladejo and multimodality of Carey Jewitt as a theoretical framework, this paper concludes with an assertion that due to the influence of consumer culture, the rhetoric of Teej songs is in flux caught between traditional practices and consumer culture. By shedding light on this shifting rhetoric of Teej songs, the study contributes to our understanding of how cultural expressions and traditional festivals are shaped by broader socio-cultural forces, highlighting the ongoing negotiation between tradition and contemporary influences in Teej songs.